Minimal energy requirement for external cardioversion and catheter ablation for long-standing persistent atrial fibrillation. Issue 1 (January 2017) - Kim, In-Soo; Kim, Tae-Hoon; Yang, Pil-Sung; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam
Abstract: Background: The minimal energy requirement ( E min ) for electrical cardioversion (ECV) reflects the atrial substrate in patients with long-standing persistent atrial fibrillation (L-PeAF), but the relationship between E min ECV and radiofrequency catheter ablation (RFCA) has not yet been studied. We hypothesize that E min ECV before ablation ( E min ECVpre) predicts clinical outcome of RFCA, and that catheter ablation reduces E min ECVpost. Methods: We included 172 patients with L-PeAF who underwent RFCA (79.7% males, 57.5 ± 10.0 years) due to AF recurrence after ECV with an anti-arrhythmic drug (AAD). ECV began with 70 J (patch electrode on anterior–posterior position) and was serially increased to 100, 150, 200, and 250 J until sinus rhythm was achieved, at an average 5.0 ± 5.6 months before RFCA. After RFCA, ECV was repeated (ECVpost) in 42 patients with recurrent AF that was not controlled by AAD. Results: (1) During 34.8 ± 20.0 months of follow-up after RFCA, 103 patients (59.9%) showed clinical recurrence of AF after RFCA. E min ECVpre was significantly higher in patients with recurrent AF (129.0 ± 58.6 J) than those who remained in sinus rhythm (94.2 ± 39.4 J, p  < 0.001). (2) E min ECVpre ≥150 J (HR = 3.31, 95% CI 2.18–5.03, p  < 0.001) and left atrial volume index (HR = 1.02, 95% CI 1.00–1.04, p  = 0.021) were significantly associated with post-RFCA recurrence. (3) Shorter post-RFCA recurrence timing was also independently related to E min ECVpre ( β  = −0.147, 95% CI −0.20 to −0.09, p  < 0.001). (4) Among 103 patients with recurrent AF after RFCA, 42 AAD-resistant AF patients underwent ECVpost. E min ECVpost (100.9 ± 50.8 J) was significantly lower than E min ECVpre (130.0 ± 66.1 J, p  = 0.006). Conclusions: Higher E min ECVpre was independently associated with clinical recurrence and earlier recurrence timing of AF after catheter ablation among patients with AAD-resistant L-PeAF. Catheter ablation for L-PeAF significantly reduces E min ECV.